Peran dan Efektivitas Lembaga Bantuan Hukum Asosiasi Perempuan Indonesia untuk Keadilan dalam Pendampingan Kasus Kekerasan Terhadap Perempuan (The Digest: Journal of Jurisprudence and Legisprudence, 2020)
Indonesia as a legal state that applies the basic principles of justice to all its people shows this by making special rules regarding human rights that are owned by everyone. One form of rights that everyone has is the right to get justice and be treated equally before the law, without discriminating against race, ethnicity, religion, or social status. So, everyone both rich and poor, has the right to get justice for the legal problems he faces, with that a legal aid agency (LBH) was formed which is regulated in Law Number 16 of 2011 concerning legal aid, the implementation of law enforcement in it (advocates) as well regulated in accordance with the rules in the code of ethics of the advocate profession. This LBH is tasked with guiding and providing legal assistance until the case is completed and the victim gets justice for their rights free of charge without being charged a fee. One of the LBH located in Jakarta, namely LBH APIK, focuses on handling legal issues against women, of the many cases, the most cases are cases of violence against women. LBH APIK Jakarta's role is to help Indonesian women understand what rights they should have as Indonesian citizens. However, there are still many pros and cons to the operation of LBH in Indonesia. Is it running effectively and really helping the people or is it just a formality institution, and this paper will discuss the effectiveness of one of the LBH's running and review in this discussion in accordance with the applicable legal rules.